2018
DOI: 10.1177/0954409717747127
|View full text |Cite
|
Sign up to set email alerts
|

An iterative methodology for the prediction of dynamic vehicle–track interaction and long-term periodic rail wear

Abstract: In this study, a versatile numerical method for the prediction of long-term growth of rail roughness is presented and its functionality is demonstrated for the development of rail corrugation on small radius curves. The procedure includes two sub-modules: (1) a time-domain model for the simulation of dynamic vehicle–track interaction in a wide range of frequencies by using a commercial software for multibody dynamics and (2) a post-calculation of sliding wear based on the Archard’s model in combination with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…This paper applies the widely used Archard wear model for analysis. 2023 The wear is proportional to the energy expended in the wheel–rail contact. This process can be described by the following equation where V w is the wear volume, k is the wear coefficient, N is the normal force, s is the sliding distance, and H is the hardness of the material.…”
Section: Comparison Of Wheel–rail Wear Developmentmentioning
confidence: 99%
“…This paper applies the widely used Archard wear model for analysis. 2023 The wear is proportional to the energy expended in the wheel–rail contact. This process can be described by the following equation where V w is the wear volume, k is the wear coefficient, N is the normal force, s is the sliding distance, and H is the hardness of the material.…”
Section: Comparison Of Wheel–rail Wear Developmentmentioning
confidence: 99%
“…He found that a high friction coefficient, high lateral creep, and stiff track are necessary conditions for friction-induced mode-coupling instability to form corrugations. Carlberger et al 17 attributed the corrugation on the lower rail of a sharp metro curve to coupled vehicle–track eigenmodes involving the bending mode of the leading wheelset.…”
Section: Introductionmentioning
confidence: 99%
“…Ignesti et al (2014) analyzed rail wear using multibody dynamics theory but did not investigate the effect of rail wear on dynamic performance. Carlberger et al (2018) established a coupled dynamic model of wheel-rail and analyzed the mechanism of corrugation caused by long-term rail wear. The above studies focus on rail wear and rail profile design.…”
Section: Introductionmentioning
confidence: 99%